2016
DOI: 10.1021/acs.biochem.5b00993
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Mycobacterium tuberculosis Rv2671 Protein as a Dihydrofolate Reductase Functional Analogue Contributing to para-Aminosalicylic Acid Resistance

Abstract: Mycobacterium tuberculosis (Mtb) Rv2671 is annotated as a 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione 5′-phosphate (AROPP) reductase (RibD) in the riboflavin biosynthetic pathway. Recently, a strain of Mtb with a mutation in the 5′ untranslated region of Rv2671, which resulted in its overexpression, was found to be resistant to dihydrofolate reductase (DHFR) inhibitors including the anti-Mtb drug para-aminosalicylic acid (PAS). In this study, a biochemical analysis of Rv2671 showed that it was able to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
(120 reference statements)
2
14
0
Order By: Relevance
“…In the case of ribD , 14 different missense mutations were found in a group of 17 variant alleles, indicating that this is likely an essential function. From studies with M. tuberculosis it is known that ribD encodes an alternative dihydrofolate reductase, with relatively low activity compared to that conferred by the bona fide dihydrofolate reductase gene, dfrA 62 . In clinical isolates of M. tuberculosis , a promoter mutation causes overexpression of ribD that is associated with resistance to the old drug, para -amino salicylic acid (PAS), and to certain DHFR inhibitors 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ribD , 14 different missense mutations were found in a group of 17 variant alleles, indicating that this is likely an essential function. From studies with M. tuberculosis it is known that ribD encodes an alternative dihydrofolate reductase, with relatively low activity compared to that conferred by the bona fide dihydrofolate reductase gene, dfrA 62 . In clinical isolates of M. tuberculosis , a promoter mutation causes overexpression of ribD that is associated with resistance to the old drug, para -amino salicylic acid (PAS), and to certain DHFR inhibitors 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies suggested that dfrA is essential in vitro in the H37Rv laboratory strain ( 5 , 6 ). More recently, it was shown that dfrA is conditionally essential and can be knocked out in H37Rv only if Rv2671 is overexpressed in trans , presumably due to its greatly reduced dihydrofolate reductase activity compared to that of DfrA ( 7 , 8 ). Our in silico analysis of the seven dfrA thyA double deletion mutants did not reveal any known Rv2671 mutations (Table S1), such as the G-to-A upstream mutation at position −12 that results in its overexpression and consequently confers PAS resistance (this mutation was incorrectly referred to as affecting position −11 in two of our prior studies [ 7 , 9 ]).…”
Section: Lettermentioning
confidence: 99%
“…Dihydrofolate reductase (PDB ID: 1DG5) helps in regulating the amount of tetrahydrofolate in the cell. Tetrahydrofolate derivatives are key components in purine and thymidylate synthesis, which is important for cell proliferation and cell growth [ 30 ].…”
Section: Computational Studiesmentioning
confidence: 99%